Pendampingan Kelompok Sadar Wisata (POKDARWIS) Karang Taruna Dalam Tata Kelola Ekowisata Danau Air Hitam Binawidya Pekanbaru - Aguswan; Eka; Trio Saputra (Jurnal Pengabdian UntukMu NegeRI, 2023)
Blackwater Lake is a lake formed from the activities of a former sand mine which is located on the Black Water Road, Binawidya Village, Binawidya District, Pekanbaru City. The existence of the lake has not been utilized by the community or the landowners for 20 years. the condition of the lake is very beautiful and clean and if it is used and developed it can be used as a new ecotourism object that can provide people's economic income, socio-culture and natural preservation in the lake area. The service is aimed at strengthening the Binawidya Karang Taruna tourism awareness group in planning, implementing, and utilizing the Black Air Lake area as a new ecotourism that provides socio-economic, cultural and natural preservation values in the local area. The results of the activities achieved were a joint consensus in determining Blackwater Lake as ecotourism and the creation of ecotourism management by the Karang Taruna Binawidya Tourism Awareness Group